Cross-border data flows in the digital economy : an analysis between the European Union General Data Protection Regulation and the Southern African Development Community Data Protection Model law - Papadopoulos, Sylvia (University of Pretoria, 2021)
Mini Dissertation (LLM (Mercantile Law))--University of Pretoria, 2020.